Service management model based on lean service tools to increase the productivity level of operations in peruvian smes in the sports sector - Andres Rivadeneyra, Santiago (2023)
The sports industry continues to show a drastic increase in its influence around the world. When mentioned, the first sector of the industry that comes to mind is the entertainment industry, with multiple million-dollar deals globally. However, the recreational sector is also growing at a significant rate, which means SMEs in this industry should try to follow this trend. This research focuses on the application of three tools that optimizes the circuit assembly time, increasing the productivity of a recreational center by allowing to expand the number of available shifts for the customers. The model presents the use of standard work as a measure to create patterns in the set-up process, 5s for the redistribution of the sporting materials, and systematic layout planning for the accommodation of the circuits and boxes. The validation method used was Arena Software and resulted in an increase of 10.82% of the productivity indicator, providing an effective service management model to be replicated in other companies. Furthermore, an economic and financial evaluation was carried through, as a validation method for the expansion of the number of available shifts, where the NPV for the proposed model resulted in USD 87,107, meanwhile the IRR achieved was 70%, and a cost-benefit indicator of 1.726.